(untitled) - Higham, James (Amsterdam, 2009)
Sport and Tourism: Globalization, Mobility and Identity marks a new era in sport tourism texts. Written by global experts whose previous collaborations have been integral to the development of the field, the book applies key social science concepts and issues relevant to the academic study of sport and tourism.
Anh văn chuyên môn TDTT
Keywords: Sports and tourism,Thể thao và du lịch